2021
DOI: 10.3390/met11040529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cd2+ on Electrodeposition of Copper in Cyclone Electrodeposition

Abstract: A strategy to determine the effect of Cd2+ on the electrodeposition of copper from a copper electrolyte by cyclone electrowinning is presented. The concentration of Cu2+ in the copper electrolyte with different Cd2+ concentrations was determined by atomic absorption spectrometry (AAS). It indicated that the current efficiency, the rate of electrodeposition, and the rate copper electrodeposition decreased with the addition of Cd2+ in the three stages of electrodeposition. The current efficiency declined from 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…S4 ). The reason for this phenomenon was that the formation of Cu(OH) 2 by Cu 2+ and OH - inhibited the progress of the reaction when the solution pH was 5, but the electrosorption of Zn 2+ promoted the desorption of inhibiting species on the electrode in the mixed solution of Cu 2+ , Cd 2+ , and Zn 2+ ( 13 , 14 ). According to these phenomena and the reduction potentials of Cu 2+ , Cd 2+ , and Zn 2+ , it could be found that the battery potential was unstable during the overdischarge of the chemical discharge.…”
Section: Resultsmentioning
confidence: 99%
“…S4 ). The reason for this phenomenon was that the formation of Cu(OH) 2 by Cu 2+ and OH - inhibited the progress of the reaction when the solution pH was 5, but the electrosorption of Zn 2+ promoted the desorption of inhibiting species on the electrode in the mixed solution of Cu 2+ , Cd 2+ , and Zn 2+ ( 13 , 14 ). According to these phenomena and the reduction potentials of Cu 2+ , Cd 2+ , and Zn 2+ , it could be found that the battery potential was unstable during the overdischarge of the chemical discharge.…”
Section: Resultsmentioning
confidence: 99%
“…12 To gain a better understanding of how imprinted polymers regulate the rate of Cd(II) adsorption, the adsorption kinetic data were fitted by pseudo-first-order model (eq 11) 45 and pseudo-second-order model (eq 12). 49 pseudo-first-order equation: (11) pseudo-second-order equation: i k j j j j j j y…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cd­(II) ion can be gradually accumulated from trace intake to excessive intake through the food chain system and eventually has certain effects on the bones, renal system, and blood system of animals and humans . Therefore, the search for the removal of Cd­(II) in the ecological environment has become a worldwide concern, which includes techniques such as chemical precipitation, reverse osmosis, membrane technologies, electrodeposition, ion exchange, photocatalysis, adsorption methods, etc. Among the available technologies, adsorption is the most effective and economical method with minimal costs, easy operation, and great recyclability .…”
Section: Introductionmentioning
confidence: 99%